State Estimation and Coordinated Control for Distributed Electric Vehicles - Chu, Wenbo (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2016)
This book tackles some of the most challenging problems in state estimation and traction coordinated control systems to improve the dynamic control performance of Distributed Electric Vehicles. The developed methods make it possible to gain more accurate information regarding the vehicle states, ensure more desirable vehicle motions and better robustness in unforeseeable driving environments. Given the impressive features of Distributed Electric Vehicles, including their simple and compact structure, short transmission chains, fast and accurate control response, modular drivetrain design etc., it is widely recognized that they represent an important future development direction and attract many of the brightest engineers and scientists. This book makes a significant contribution to the design of safer and more efficient vehicles.